Pengaruh Pupuk Organik Berbasis Azolla, Fosfat Alam dan Abu Sekam terhadap Hasil Padi dan Sifat Kimia Tanah Alfisol - Sudadi Sudadi; Sumarno Sumarno; Wiki Handi (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
Effect of Azolla Based - Organic Fertilizer, Rock Phosphate and Rice Hull Ash on Rice Yield and Chemical Properties of Alfisols. The application of chemical fertilizer for long time may adverse soil environment. Organic agriculture, for example combination use of azolla based-organic fertilizer, phosphate rock and rice hull ash, was one of ways that able to recover it. Research was conducted in Sukosari, Jumantono, Karanganyar while soi chemical properties analysis was analysed in Soil Chemistry and Fertility Laboratory, Fac. of Agriculture, Sebelas Maret University April to November 2013. Research design used was RAKL with 5 treatments, each repeated 5 times. The treatments applied were P0 (control), P1 ( azola inoculum dosage 250 g/m2 + phosphate rock + rice hull ash equal to 150 kg/ha KCl), P2 (azola inoculum dosage 500 g/m2 + phosphate rock equal to 150kg/ha, SP-36 + rice hull ash equal to 100 kg/ha KCl), P3 (manure dosage of 5 ton/ha),P4 (Urea 250 kg/ha + SP-36 150 kg/ha + KCl 100 kg/ha). Data analysed statistically by F test (Fisher test) with level of confident 95% followed by DMRT (Duncan Multiple Range Test) if any significant differences. The result showed that the treatment combination of azolla, phosphate rock and rice hull ash increase soil organic matter content, cation exchange capacity, available-P and exchangeable-K as well as rice yield ( (at harvest-dry grain weight and milled-dry grain weight).